2016
DOI: 10.1007/s11101-015-9452-y
|View full text |Cite
|
Sign up to set email alerts
|

Review on Saussurea laniceps, a potent medicinal plant known as “snow lotus”: botany, phytochemistry and bioactivities

Abstract: Saussurea laniceps (Compositae), commonly known as "cotton-headed snow lotus", is the most effective "snow lotus" used in both Tibetan and Chinese folk medicine. It performs outstandingly in treating rheumatoid arthritis, which mainly is credited for its anti-inflammatory and anti-nociceptive efficacy, as explained by modern pharmacological studies. Extracts of the herb, including umbelliferone and scopoletin, exert such effects in various in vivo and in vitro studies. Besides the two chemicals above, more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…[14,35] Sub-cluster II consists of three phenylpropanoids, chlorogenic acid (peak 3), syringin (peak 5) and 1,5-dicaffeoylquinic acid (peak 13), content levels of which, in decreasing sequence, are SL, SI and SM. Analytes were separated into four groups, based on their respective abundance levels in every sample, interestingly corresponding to their chemical structures.…”
Section: Hierarchical Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…[14,35] Sub-cluster II consists of three phenylpropanoids, chlorogenic acid (peak 3), syringin (peak 5) and 1,5-dicaffeoylquinic acid (peak 13), content levels of which, in decreasing sequence, are SL, SI and SM. Analytes were separated into four groups, based on their respective abundance levels in every sample, interestingly corresponding to their chemical structures.…”
Section: Hierarchical Cluster Analysismentioning
confidence: 99%
“…[7] Some snow lotus healthcare products are even adulterated with other herbs, causing an inevitable concern to public health. [14][15][16] The more we looked into the three medicinal sources, the more we were convinced of the need for an in-depth investigation of the chemical constituents of such raw herbal products as the basis for extending their medical applications [17][18][19] as well as preventing falsification of the products on the market. [8][9][10] Some studies have authenticated different botanical origins of snow lotus medicines by observing macroscopic and microscopic features; [7,11,12] others have preliminarily analyzed chemical components and compared their pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Resent researches showed that this herb has anti-inflammatory and analgesic, antimetastasis and anti-cancer activities in vitro. [5][6] We have been carried out in vivo study to screen anti-tumor activity using a hollow fiber assay for developing lead compounds of the pancreatic cancer drug, because pancreatic cancer is quite advanced, complete surgical removal is not possible and there is no optimum chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Commission, 2010; Yi et al, 2010, Chik et al, 2015Chen et al, 2016). Saussurea involucrata and Saussurea laniceps are two species of -snow lotus‖.…”
mentioning
confidence: 99%